Role of Home Blood Pressure Monitoring in Treatment Follow-up by Hypertensive Patients Cohort - Nupur, Farjana Pervin; Hoque, Mohammad Mahfuzul; Najifa, Wafia; Afrin, Sajia; Biswas, Sarmistha; Masuduzzaman, S M; Deb, Sudip Ranjan; Miah, Md Titu (Journal of Medicine, 2024)
Background: The main benefit of home-based blood pressure monitoring (HBPM) is the potential approach to reduce the risk of white-coat hypertension (HTN) and to encourage patients to take ownership of their condition. This study was conducted to assess the role of HBPM in treatment follow-up in a cohort of hypertensive patients. Materials and methods: This was a prospective observational study conducted from December 2017 to May 2018. A total of 100 patients fulfilling the inclusion and exclusion criteria were selected by purposive sampling from Medicine Outdoor of Dhaka Medical College Hospital (DMCH). In total, 100 hypertensive patients were enrolled, and informed consent was obtained. Subsequently, the study subjects received information and training on BP self-management and performed 2 resting measurements per day for 4 days per week for 3 months. All measurements were performed using validated BP monitors.The study endpoints included patient awareness, attainment of BP goals, adherence to antihypertensive treatment, lifestyle modification, assessment of discrepancy between office and HBPM, and white coat HTN or masked HTN at 3 months. SPSS version 22.0 was used for data analysis and reporting. Results: Overall, the mean age was 57.76 ±12.60 years with a range of 34 – 80 years. Males were more prevalent than females, and the ratio was 1.17:1. The majority of cases (76.0%) had established HTN with a history of taking medication, whereas others were non-compliant with medications. Among them 47% had obesity, and 24% had diabetes mellitus. Of the patients, 91% adherence to HBP monitoring, 84.0% adherence to medication, and 75.0% achieved their target BP. The achievement of target blood pressure was significantly higher among the study subjects who adhered to HBP monitoring, and the p-value was < 0.04 (Fisher’s Exact test). Conclusion: In a cohort of patients with arterial hypertension, information, and training on BP self-measurement and direct involvement of patients using HBPM led to improvement in BP control and could be an effective method by incorporating it into the usual care of hypertensive patients in the hypertension management center of the community. J MEDICINE 2024; 25: 17-23